2019
DOI: 10.1021/acsami.9b12783
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Solution Deposition of Pt-Pd Titania Nanocomposite Coatings for Light-Assisted Formic Acid Electro-Oxidation

Abstract: Many nanofabrication processes require sophisticated equipment, elevated temperature, vacuum or specific atmospheric conditions, templates, and exotic chemicals, which severely hamper their implementation in real-world applications. In this study, we outline a fully wet-chemical procedure for equipping a 3D carbon felt (CF) substrate with a multifunctional, titania nanospike-supported Pt-Pd nanoparticle (Pt-Pd-TiO2@CF) layer in a facile and scalable manner. The nanostructure, composition, chemical speciation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 74 publications
2
17
0
Order By: Relevance
“…Building up on the fact, that sample Pd 20 Pt 80 showed the quickest stripping of surface oxides, we conducted a COstripping experiment after 1 h of indirect poisoning with potentiostatic application in 0.1 m formic acid (HCOOH). Similar to a recent study in our research group, [53] our experiment compares the CO-stripping capabilities of our Pd 20 Pt 80 NTNW to the pure Pt NTNW (Pd 0 Pt 100 ). The plotted results can be seen in Figure 9 of the Supporting Information.…”
Section: Tailoring the Composition Of Pd/pt-nt Catalysts For Methanolsupporting
confidence: 58%
See 1 more Smart Citation
“…Building up on the fact, that sample Pd 20 Pt 80 showed the quickest stripping of surface oxides, we conducted a COstripping experiment after 1 h of indirect poisoning with potentiostatic application in 0.1 m formic acid (HCOOH). Similar to a recent study in our research group, [53] our experiment compares the CO-stripping capabilities of our Pd 20 Pt 80 NTNW to the pure Pt NTNW (Pd 0 Pt 100 ). The plotted results can be seen in Figure 9 of the Supporting Information.…”
Section: Tailoring the Composition Of Pd/pt-nt Catalysts For Methanolsupporting
confidence: 58%
“…The NP seeds initiate the electroless plating reaction, which at later stages advances autocatalytically due to the catalytic qualities of the metal deposit (Figure ). From our experience, the Pd seeds play a marginal role for the overall stoichiometry: They only cover a small fraction of the nanotubes’ surface and shrink or dissolve under subtle galvanic exchange during electroless plating, making them hard to detect for most bulk analysis techniques. EDS measurements did not show any Pd content in the Pd 0 Pt 100 NTNW sample, suggesting that the Pd seeding only affects the catalyst performance to a minor degree.…”
Section: Resultsmentioning
confidence: 99%
“…During electroless plating, galvanic displacement must be considered as a possible side reaction which can leach the seeds [45] or previously deposited metals. This undermines the feasibility of certain metal deposition sequences, but can also serve synthetic purposes: Galvanic displacement can introduce new metals to previously plated nano‐objects [187] (Figure 10D), and can accompany electroless plating reactions ( e. g ., causing elemental mixing in Pd−Pt nanoparticles) [45] . The composition and structure of plated multimetallic nanomaterials can also be modified through selective chemical etching [115,118,187] …”
Section: Nanomaterials Synthesismentioning
confidence: 99%
“…While such reactions can be more forgiving in terms of metastability (the presence of evenly distributed sites for metal deposition can help staying below the concentration threshold for spontaneous homogeneous nucleation), [34] the underlying reaction mechanism is identical. Given this close relationship, it is not astounding that electroless plating is wellsuited for creating materials which are typically obtained by seed-mediated colloidal growth (e. g., bimetallic nanoparticles, [13,45] anisotropic nanostructures). [19,20,46] To avoid confusion, it should be noted that electroless deposition and electroless plating are often used interchangeably, and that methods such as galvanic displacement are frequently termed as electroless deposition.…”
Section: The Mechanism Of Electroless Platingmentioning
confidence: 99%
“…In addition, as a part of mechanism research, photothermal effect under light illumination has to be mentioned. [77,[95][96][97][98][99][100] Several works have reported that photothermal effect is in negligible, although the photoelectrochemcial cell was kept at a constant temperature using a circulating water system. Recently, Yang et al used surface-enhanced Raman scattering to detect the real temperature on the Au@2Pt NPs core-shell catalyst which is measured to be as high as 80 and 95 C after illuminating with 530 AE 10 nm light for 25 min with a power density of 10 and 30 mW cm À2 .…”
Section: Photoelectrocatalysis Mechanismmentioning
confidence: 99%